The Effect of Response Inhibition Training on Risky Decision-Making Task Performance - Xu, Pengbo; Wu, Di; Chen, Yuqin; Wang, Ziwei; Xiao, Wei (Frontiers in Psychology, 2020)
Response inhibition is an important component of executive function and plays an indispensable role in decision-making and other advanced cognitive processes. At the same time, we need an effective way to improve decision-making in the face of complex and limited information. This study mainly explored the influence of response inhibition training on college students' risky decision-making. The recruited students were randomly divided into the training group (n=28) and the control group (n=28). The training group engaged in Go/NoGo and stop-signal tasks for 2 weeks, while the control group was given the task of reading and summarizing popular science articles related to self-control. The Stroop task and Balloon Analog Risk Task were used to evaluate the pretest and posttest performance in inhibitory control and risky decision-making tasks, respectively, for all subjects. The results showed that response inhibition training can be effectively transferred to interference control task performance. The results showed that both the reward acquired and adjusted Balloon Analog Risk Task score (adj BART) significantly improved compared to the pretest in the training group, while the control group showed no significant differences in the reward acquired and the adj BART between the pretest and the posttest. Although response inhibition training increased risky behaviors in the Balloon Analog Risk Task, it substantially reduced overly conservative behaviors, and participants gained more money.